O potrzebie euro-nowelizacji Konstytucji RP: [About the need of euro-amendment to the Constitution of Poland] (Studia Prawnicze / The Legal Studies, 2010)
Akcesja każdego państwa w struktury Unii Europejskiej wymaga, w krótszej bądź dłuższej perspektywie czasowej, rewizji obowiązujących postanowień konstytucyjnych. Uczestnictwo państwa w Unii, obejmującej swoim zasięgiem corazwięcej sfer życia społeczno-gospodarczo-politycznego wymaga bowiem równieżi ingerencji w tekst ustawy zasadniczej, choć oczywiście ingerencja ta nie musi sięodbyć w jakimś jednym, określonym momencie, ani też przybierać jakiegoś zuniformizowanego, homogenicznego kształtu. Mimo wszystko jednak postępującasukcesywnie i konsekwentnie integracja, a w rezultacie utworzenie wspólnegoorganizmu unijnego, stawia na porządku dziennym konieczność dostosowaniawcześniej czy później prawa krajowego, w tym również tego mającego postać kon-stytucji do wymagań wspólnotowych (unijnych). Wieloaspektowość, a zarazemcoraz dalej posunięta detalizacja zasad partycypacji państwa w Unii Europejskiej z jednej strony, z drugiej zaś przybierająca coraz więcej form Unia, która dawnotemu przestała już być jedynie gremium współpracy gospodarczej, prowadzi bowiem do objęcia gorsetem regulacji normatywnej również i tej sfery, która do tejpory była zarezerwowana wyłącznie dla ustawodawcy krajowego działającego wkwalifikowanej formie ustrojodawcy. Today, the necessity of adapting the constitution to certain general standards or models is clear. No constitution, including the Constitution of Poland, is a fully independent and autonomous act separate from a broader background. At the present moment, such background is created by e.g. the international models and general rules, and solutions applied in a democratic constitutional state. Every constitution creator wishes to form a truly modern act that will be adequate to the need of the moments and, at the same time, properly (democratically) legitimized, which must respect certain, at least the minimum requirements in the scope of defining the catalogue of principal rules or rights and freedoms of an individual. The so–called standard in constitutional law is an unquestionable fact. This general standard, being the effect of globalization and European integration, can be called a form of Euro–amendment to the Constitution in the broadest possible sense of this expression. Every country must respect it, if it wishes to participate in the family of democratic countries. However, the proper Euro–amendment has a much more modest reach and it covers the part of constitutional matter which pertains to the participation of a state in the European Union directly. The Euro–amendment understood in this way can be divided into the widely understood Euro–amendment (sensu largo), which will contain procedures, e.g. of a country accession to the Union and enforcement of its rights and the narrow Euroamendment (senstu stricto), which should be understood as adaptation of the constitution to the mechanism of a country’s accession to the Economic and Monetary Union and, in consequence, replacement of the national currency with Euro. In Poland, proper Euro–amendment has not been introduced in the wide or in the narrow sense. It seems, however, that it is more and more necessary not only owing to the deepening participation of Poland in the European Union structures but, most of all, owing to the willingness (and the need resulting from the accession treaty) to accept the Euro currency.